ESP Teacher`s Self-Reflection: Teacher Agency and Frustration of the Enactment - Hidayati, Sari (Indonesian Journal of EFL and Linguistics, 2024)
Self-reflection is an integral element of teacher professional development and a viable means for sharpening teacher knowledge and skills for subsequent pedagogic applications and improving student learning outcomes. While self-reflection is an individual professional endeavor, it is obviously tied to the professional contexts. As such, the notion of self-reflection is inherently tied to improving teachers` professional agency. However, there is potential for frustration in the enactment of teacher agency if practitioners are not cautious of the contextual constraints within which they have to exercise their agency. For example, changes that require enactment may have wider implications for institutions of employment, institutional policies of assessment and teaching, colleagues, and stakeholders. This paper aims to get an in-depth description of a teacher`s reflection on her professional practice as an English for Specific Purposes (ESP) teacher at the university level. This study adopted a qualitative case study as the research design and collected data using a semi-structured interview with an English teacher for specific purposes in the tertiary sector in Yogyakarta, Indonesia. The findings of this single case study chartered the frustrations experienced by English teachers in enacting agency for specific purposes in Indonesian tertiary education. These are discussed in relation to the implications they have for teacher agency, professional development, English for Specific Purposes classroom practice, and future research.